Sosialisasi Posisi Kerja yang Baik untuk Mencegah Potensi Risiko Cedera di CV Panglong Kayu Putri Damai Tanjung Kelas - Zulfikar Zulfikar; Rinaldi Prima Saputra; Fatimah Wahab Aliun (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The implementation of ergonomic principles is an important preventive strategy to reduce the risk of occupational injuries in the wood-processing industry, where manual material handling activities are predominant. This Community Service Program aimed to improve workers' knowledge and skills regarding ergonomic working postures to prevent Musculoskeletal Disorders (MSDs) at CV Panglong Kayu Putri Damai Tanjung Kelas, South Lampung. The program involved 50 workers and employed a one-group pre-test and post-test approach, interactive lectures, demonstrations of proper lifting techniques, role-playing, stretching exercises, and the installation of educational posters in the workplace. The evaluation results indicated a significant improvement in participants' knowledge, as the proportion of workers in the good knowledge category increased from 10% to 74%, while the low knowledge category decreased from 54% to 4%. Field observations also demonstrated improved ability among workers to apply ergonomic working postures during production activities. The program confirms that practice-based ergonomic education effectively strengthens occupational safety culture and supports injury prevention in the wood-processing industry.